(Un)wanted partners: Muslim politics and third front coalitions in India - Emmerich, Arndt (India review, 2023)
Drawing on qualitative fieldwork with two Islamist movements in India since 2011, this article contributes to a better understanding of how Muslim community leaders try to spearhead third front alliances with secular and religious minorities through discourses of shared political and economic victimhood and the provision of protection against the assertions of Hindu nationalists in an era of unprecedented Hindu vote consolidation. While such alliances exist, the paper analyzes a new trend within Muslim politics that promotes a political departure from the traditional patronage of the Indian National Congress (INC) and other low-caste and socialist parties, which have historically represented the Muslim masses. I then discuss the limitations of these third front leadership ambitions, whereby Islamist movements are seen as incompatible with gender equality and secular norms. Theoretically, the paper informs the academic debate on coalition-building processes within social movement theory (SMT), which has partially ignored the role of conservative religious actors in democratic as well as authoritarian systems.
Gesehen am 22.12.2023